PEMBELAJARAN METACOGNITIVE SCAFFOLDING SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP DALAM MEMECAHKAN MASALAH - Muhamad Zulfikar Mansyur; Depi Ardian Nugraha (LPPM Universitas Bina Bangsa, 2021)
Critical thinking ability is an important ability to have. However, students' mathematical critical thinking skills are still low. Efforts that can be applied are through the Metagontive Scaffolding learning approach. The Metcagontive Scaffolding approach has been proven to be able to improve mathematical communication skills, mathematical literacy, and self-efficacy. This study was conducted to test whether Metagontive Scaffolding can improve the mathematical critical thinking skills of junior high school students better than direct learning. This study uses a quasi-experimental method with a nonequivalent control group design. The population in this study were all eighth grade students in one of the public junior high schools in Bandung. This study uses two classes as a sample from a number of class VIII randomly graded. The data in this study were obtained through the results of the answers to students' mathematical critical thinking abilities. significantly compared to students who participated in direct learning